Finite element analysis of a composite crash box subjected to low velocity impact - Shaik Dawood, Mohd. Sultan Ibrahim; Ahmad Ghazilan, Ahmad Luqman; Shah, Qasim Hussain (IOP Publishing Ltd., 2017)
In this work, finite element analyses using LS-DYNA had been carried out to investigate the energy absorption capability of a composite crash box. The analysed design incorporates grooves to the cross sectional shape and E-Glass/Epoxy as design material. The effects of groove depth, ridge lines, plane width, material properties, wall thickness and fibre orientation had been quantitatively analysed and found to significantly enhance the energy absorption capability of the crash box.